Ryanodine receptor remodeling in cardiomyopathy and muscular dystrophy caused by lamin A/C gene mutation - Dridi, Haikel; Wu, Wei; Reiken, Steven R; Ofer, Rachel M; Liu, Yang; Yuan, Qi; Sittenfeld, Leah; Kushner, Jared; Muchir, Antoine; Worman, Howard J; Marks, Andrew R (Human molecular genetics, 2020)
Mutations in the lamin A/C gene (LMNA), which encodes A-type lamins, cause several diseases called laminopathies, the most common of which is dilated cardiomyopathy with muscular dystrophy. The role of Ca2+ regulation in these diseases remain poorly understood. We now show biochemical remodeling of the ryanodine receptor (RyR)/intracellular Ca2+ release channel in heart samples from human subjects with LMNA mutations, including protein kinase A-catalyzed phosphorylation, oxidation and depletion of the stabilizing subunit calstabin. In the LmnaH222P/H222P murine model of Emery-Dreifuss muscular dystrophy caused by LMNA mutation, we demonstrate an age-dependent biochemical remodeling of RyR2 in the heart and RyR1 in skeletal muscle. This RyR remodeling is associated with heart and skeletal muscle dysfunction. Defective heart and muscle function are ameliorated by treatment with a novel Rycal small molecule drug (S107) that fixes ‘leaky’ RyRs. SMAD3 phosphorylation is increased in hearts and diaphragms of LmnaH222P/H222P mice, which enhances NADPH oxidase binding to RyR channels, contributing to their oxidation. There is also increased generalized protein oxidation, increased calcium/calmodulin-dependent protein kinase II-catalyzed phosphorylation of RyRs and increased protein kinase A activity in these tissues. Our data show that RyR remodeling plays a role in cardiomyopathy and skeletal muscle dysfunction caused by LMNA mutation and identify these Ca2+ channels as a potential therapeutic target.